Biodegradation of Gossypol by Aspergillus terreus-YJ01 - Yao Jiang; Xinyue Du; Qianqian Xu; Chunhua Yin; Haiyang Zhang; Yang Liu; Xiaolu Liu; Hai Yan (Microorganisms, 2023)
Gossypol, generally found in the roots, stems, leaves, and, especially, the seeds of cotton plants, is highly toxic to animals and humans, which inhibits the use of cotton stalks as a feed resource. Here, a promising fungal strain for biodegrading gossypol was successfully isolated from the soil of cotton stalk piles in Xinjiang Province, China, and identified as Aspergillus terreus-YJ01 with the analysis of ITS. Initial gossypol of 250 mg·L−1 could be removed by 97% within 96 h by YJ01, and initial gossypol of 150 mg·L−1 could also be catalyzed by 98% or 99% within 36 h by the intracellular or extracellular crude enzymes of YJ01. Sucrose and sodium nitrate were found to be the optimal carbon and nitrogen sources for the growth of YJ01, and the optimal initial pH and inoculum size for the growth of YJ01 were 6.0 and 1%, respectively. To further elucidate the mechanisms underlying gossypol biodegradation by YJ01, the draft genome of YJ01 was sequenced using Illumina HiSeq, which is 31,566,870 bp in length with a GC content of 52.27% and a total of 9737 genes. Eight genes and enzymes were predicted to be involved in gossypol biodegradation. Among them, phosphoglycerate kinase, citrate synthase, and other enzymes are related to the energy supply process. With sufficient energy, β-1, 4-endo-xylanase may achieve the purpose of biodegrading gossypol. The findings of this study provide valuable insights into both the basic research and the application of A. terreus-YJ01 in the biodegradation of gossypol in cotton stalks.